Socioeconomic inequality undermines relationship quality in romantic relationships. (May 2020) - Cho, Minha; Impett, Emily A.; Campos, Belinda; Chen, Serena; Keltner, Dacher
The present research tests how socioeconomic inequality (within romantic relationships) predicts relationship quality and observable expressions of emotion—examining longitudinal self-report and behavioral data from both partners of romantic couples. In Part 1, we examined the romantic partners' self-reports of relationship quality at baseline and after three and a half months. In keeping with prior research on how power inequality undermines relationship satisfaction, couples defined by greater socioeconomic inequality showed a decline in relationship quality over time. In Part 2, we examined observer ratings of emotional expressions in the romantic partners' conversations in the laboratory. Here, we found greater expression of negative emotion in the conversations of couples defined by greater inequality. Importantly, it was inequality itself—rather than whether one has higher or lower socioeconomic status than the partner—that significantly predicted changes in relationship quality and observable expressions of negative emotion. These findings have implications for how deepening economic inequality may manifest in the weakening of intimate bonds—the quality of which is central to the well-being of individuals and broader society.